THE USE OF PROVERBS IN HIP-HOP MUSIC: THE EXAMPLE OF YORUBA PROVERBS IN 9ICE’S LYRICS - Akande, Akinmade Timothy; Mosabalaye, Adebayo (Proverbium - Yearbook, 2014)
Proverb is a canonized oral form that contains the mores, wisdom and worldview of a particular society. As an oral form of the Yoruba people of Southwestern Nigeria, it is used to (re)create identity, interrogate reality, and mediate real and artistic discourses. It is against this background that this paper examines the use of, and modes of mediation of Yoruba proverbs in the song-poetry of Abolore Adegbola Akande, a popular Nigerian hip-hop artiste whose stage name is 9ice. The data for the paper are selected song-texts of 9ice downloaded from different websites. The proverbs in the selected songs were identified and classified into groups. The study reveals that 9ice uses Yoruba proverbs to perform various global speech acts such as boasting, dissing, warning and teaching.